2018
DOI: 10.1016/j.stem.2018.06.015
|View full text |Cite|
|
Sign up to set email alerts
|

Th17 Lymphocytes Induce Neuronal Cell Death in a Human iPSC-Based Model of Parkinson’s Disease

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder characterized by the progressive degeneration of midbrain neurons (MBNs). Recent evidence suggests contribution of the adaptive immune system in PD. Here, we show a role for human T lymphocytes as cell death inducers of induced pluripotent stem cell (iPSC)-derived MBNs in sporadic PD. Higher Th17 frequencies were found in the blood of PD patients and increased numbers of T lymphocytes were detected in postmortem PD brain tissues. We modeled this finding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
238
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 237 publications
(264 citation statements)
references
References 39 publications
11
238
4
2
Order By: Relevance
“…An increased number of myeloid cells may be related to either an enhanced proliferation of resident microglia or infiltration of peripheral monocytes and macrophages. Infiltration of peripheral cells in the brain parenchyma was identified in human post‐mortem brain tissue of PD patients as well as its corresponding mouse models . Recent studies have identified distinct macrophage subsets located in the choroid plexus, the meninges as well as the perivascular space expressing similar surface markers and contributing to defense mechanisms in neurodegenerative diseases .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased number of myeloid cells may be related to either an enhanced proliferation of resident microglia or infiltration of peripheral monocytes and macrophages. Infiltration of peripheral cells in the brain parenchyma was identified in human post‐mortem brain tissue of PD patients as well as its corresponding mouse models . Recent studies have identified distinct macrophage subsets located in the choroid plexus, the meninges as well as the perivascular space expressing similar surface markers and contributing to defense mechanisms in neurodegenerative diseases .…”
Section: Discussionmentioning
confidence: 99%
“…The classical markers commonly used to identify resting and activated myeloid cells, such as IBA1, CD11b and CD68, do not allow exact distinction between resident microglia and infiltrated myeloid cells . In contrast, recruitment of peripheral myeloid cells as well as lymphocytes is described in human post‐mortem brain tissue of PD patients as well as in respective in vitro and in vivo models . Besides myeloid cells, astrocytes are also activated by oligodendroglial α‐syn leading to morphological changes and cytokine production .…”
Section: Introductionmentioning
confidence: 99%
“…Respective fibroblasts were previously reprogrammed from controls and patients suffering from PD (Fig. B) . HiPSCs and smNPCs were cryopreserved via slow‐rate freezing in suspension and adherent vitrification in the TWIST substrate and analyzed after thawing (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The smNPCs were generated using an adapted version of a published protocol for a dual‐SMAD‐based generation of midbrain neurons from hiPSCs (Fig. A) . The cryopreservation experiments were designed using the same groups and freezing conditions as for the hiPSCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study conducted in mice demonstrates a clonal T cell expansion within the brain of old mice with high levels of IFN-γ, suggesting a role for T cellderived IFN-γ in the age-dependent decline of brain function 65 . Given the presence of T lymphocytes in PD brains and the increasing evidence pointing towards a role for T cell responses in disease pathogenesis 66,67,68 , T-cells could be the main source of IFN-γ, which, in turn, induces LRRK2 expression in neurons and microglia, leading to neuronal damage and inflammatory reactions. Thus, further studies are warranted to investigate the role of IFN signaling in specific brain regions and the role of IFN-γ producing T-cells in ageing and PD.…”
Section: Discussionmentioning
confidence: 99%